2016
DOI: 10.1053/j.gastro.2015.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Tenofovir Disoproxil Fumarate and Peginterferon α-2a Increases Loss of Hepatitis B Surface Antigen in Patients With Chronic Hepatitis B

Abstract: A significantly greater proportion of patients receiving TDF plus peginterferon for 48 weeks had HBsAg loss than those receiving TDF or peginterferon alone. ClinicalTrials.gov ID NCT01277601.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
284
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(309 citation statements)
references
References 32 publications
(19 reference statements)
16
284
1
3
Order By: Relevance
“…1,130 In a recent randomised controlled trial, the 72-week HBsAg loss rates were superior in the PegIFNa and TDF treated patients compared to those observed in patients receiving PegIFNa alone or TDF alone (9% vs. 3% vs. 0%) but the overall rates were low and mainly confined to genotype A patients. 62 pretreatment with NA improves the rates of sustained response to PegIFNa. 130,132,133 The multicentre ARES study demonstrated that a 24-week course of PegIFNa, given to a small group of HBeAg-positive patients who were on ETV therapy for only 24 weeks, can improve the kinetics of HBeAg, HBV DNA and HBsAg, compared to those on ETV monotherapy, but a PegIFNa monotherapy arm was missing.…”
Section: Na Plus Pegifna Recommendationsmentioning
confidence: 97%
See 2 more Smart Citations
“…1,130 In a recent randomised controlled trial, the 72-week HBsAg loss rates were superior in the PegIFNa and TDF treated patients compared to those observed in patients receiving PegIFNa alone or TDF alone (9% vs. 3% vs. 0%) but the overall rates were low and mainly confined to genotype A patients. 62 pretreatment with NA improves the rates of sustained response to PegIFNa. 130,132,133 The multicentre ARES study demonstrated that a 24-week course of PegIFNa, given to a small group of HBeAg-positive patients who were on ETV therapy for only 24 weeks, can improve the kinetics of HBeAg, HBV DNA and HBsAg, compared to those on ETV monotherapy, but a PegIFNa monotherapy arm was missing.…”
Section: Na Plus Pegifna Recommendationsmentioning
confidence: 97%
“…Theoretically, a combined NA and PegIFNa approach may provide advantages by combining the potent antiviral effect of NA plus the immune modulation of IFNa. 1,56,62,63 The evidence for superiority of such a combined approach, however, is lacking, and there are still many unresolved issues with respect to patient selection, timing, as well as the duration of the combination strategy, which may be addressed in future studies.…”
Section: 5657mentioning
confidence: 99%
See 1 more Smart Citation
“…PEG-IFN monotherapy has been reported to result in hepatitis B e antigen (HBeAg) seroconversion in 29 to 32% of patients and in hepatitis B surface antigen (HBsAg) loss in 3 to 7% of patients at 24 weeks after completion of treatment (11,14). Combination therapy with both an NA and PEG-IFN-␣-2a has been shown to result in greater viral decline and HBeAg loss than NA therapy alone (15)(16)(17)(18) and resulted in reduced HBV cccDNA in chronic hepatitis B patients (19,20). Therefore, we hypothesized that combination therapy with high doses of NA and PEG-IFN could eliminate HBV infection in an immunodeficient animal model.…”
Section: H Epatitis B Virus (Hbv) Infection Is the Most Common Chronimentioning
confidence: 99%
“…Increasingly, clinical studies evaluating a finite duration of NA therapy are being undertaken [9]. With new therapeutic targets identified [10], future HBV therapy is likely to be more individualized and utilize sequential or combinations of drugs that target specific host and viral pathways to achieve functional cure. With these future therapies, reports from high-quality ''real-world'' cohorts will continue to inform practice by providing safety and effectiveness data across diverse treatment settings and in a broader array of patients.…”
mentioning
confidence: 99%